2022
DOI: 10.3390/vetsci9040164
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Digestibility and Fecal Quality in Beagle Dogs Fed Meat and Bone Meal Added to Dry Food

Abstract: Meat and bone meal (MBM) is one animal by-product used in pets. This study purposed to provide information on MBM including either coarsely (MBMc) or finely (MBMf) ground with regard to diet digestibility and fecal characteristics in dogs. Three different levels of MBM (6%, 12% and 24%) of each grinding form (MBM6, MBM12 and MBM24) were added to a basic diet. Six Beagle dogs (body weight 16.7 kg ± 0.42) participated in a Latin Square experiment. Each trial began with the animals adapting to the food for a five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Interestingly, the particle size seemed to have no effect on the protein digestibility. A previous study by Abd El-Wahab et al [ 14 ] also reported that the particle size or degree of grinding of poultry by-product inclusion in dog food had no effect on the apparent digestibility of crude protein and crude fat. In the present work, when considering particle size, the ether extract was lower in the coarse diet compared to the fine and very fine diets (485 g/kg DM vs. 576 and 547 g/kg DM, respectively).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, the particle size seemed to have no effect on the protein digestibility. A previous study by Abd El-Wahab et al [ 14 ] also reported that the particle size or degree of grinding of poultry by-product inclusion in dog food had no effect on the apparent digestibility of crude protein and crude fat. In the present work, when considering particle size, the ether extract was lower in the coarse diet compared to the fine and very fine diets (485 g/kg DM vs. 576 and 547 g/kg DM, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…The coarse grinding may reduce nutrient exposure to digestive enzymes regarding protein digestibility [ 13 ]. Moreover, the degree of grinding could affect the fecal quality in dogs [ 14 ]. It is commonly known that grinding is a main concern during food processing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, LC2 and LC4 had significantly lower OM digestibility compared to LC0; however, only LC4 had significantly lower NFE digestibility compared to LC0 and LC2. Many factors can affect the diet digestibility, as well as nutrient quality and chemical composition [ 31 , 36 , 37 ]. Regarding the fiber content, Bednar et al [ 38 ] and Kienzle et al [ 39 ] found that digestibility of OM was lower for the diet containing a higher level of dietary fiber, which could possibly reduce nutrient digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…The “food intake assessment” (palatability and speed of food intake) was divided into three scores in accordance with Abd El-Wahab et al [ 31 , 32 ]. Briefly, score 1 = lowest acceptance; score 2 = moderate acceptance; score 3 = maximum acceptance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation